Excitonic Properties of Chemically Synthesized 2D Organic–Inorganic Hybrid Perovskite Nanosheets. Issue 18 (25th March 2018) - Zhang, Qi; Chu, Leiqiang; Zhou, Feng; Ji, Wei; Eda, Goki
Abstract: 2D organic–inorganic hybrid perovskites (OIHPs) represent a unique class of materials with a natural quantum‐well structure and quasi‐2D electronic properties. Here, a versatile direct solution‐based synthesis of mono‐ and few‐layer OIHP nanosheets and a systematic study of their electronic structure as a function of the number of monolayers by photoluminescence and absorption spectroscopy are reported. The monolayers of various OIHPs are found to exhibit high electronic quality as evidenced by high quantum yield and negligible Stokes shift. It is shown that the ground exciton peak blueshifts by ≈40 meV when the layer thickness reduces from bulk to monolayer. It is also shown that the exciton binding energy remains effectively unchanged for (C6 H5 (CH2 )2 NH3 )2 PbI4 with the number of layers. Similar trends are observed for (C4 H9 NH3 )2 PbI4 in contrast to the previous report. Further, the photoluminescence lifetime is found to decrease with the number of monolayers, indicating the dominant role of surface trap states in nonradiative recombination of the electron–hole pairs. Abstract : Large ultrathin crystals of (C4 H9 NH3 )2 PbI4 (C4PI) and (C6 H5 (CH2 )2 NH3 )2 PbI4 (PEPI) with thickness ranging from a single monolayer to tens of monolayers are synthesized from solution phase. Photoluminescence spectroscopy of individual nanosheets reveals that the electronic gap and exciton binding energy of PEPI are nearly independent of the number of layers, indicating the absence of interlayer screening effects.